Periodontal ligament distraction: A simplified approach for rapid canine retraction - K C Prabhat; Sandhya Maheshwari; N D Gupta; Sanjeev K Verma; Lata Goyal (Wolters Kluwer Medknow Publications, 2012)
Distraction osteogenesis is a method of inducing new bone formation by applying mechanical strains on preexisting bone. The process of osteogenesis in the periodontal ligament during orthodontic tooth movement is similar to the osteogenesis in the midpalatal suture during rapid palatal expansion. A new concept of "distracting the periodontal ligament" is proposed to elicit rapid canine retraction in two weeks. At the time of first premolar extraction, the interseptal bone distal to the canine was undermined with a bone bur, grooving vertically inside the extraction socket along the buccal and lingual sides and extending obliquely toward the socket base. Then, a tooth-borne, custom-made, intraoral distraction device was placed to distract the canine distally into the extraction space. It was activated 0.5 mm/day, immediately after the extraction. Canine was distracted 6.5 mm into the extraction space within two weeks.